ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT MAHASISWA MELAKUKAN TINDAKAN WHISTLEBLOWING - Fany Imelda Imlabla; Nicolas Ahuluheluw; Selva Temalagi (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2021)
This study aims to test empirically the effect of attituteds, subjective norms, behavior control and personality types on the intentions. The population in this study is the active student of Accounting Study Program PSDKU, Pattimura University in Aru Archipelago Regency. The sample in this study is accounting students in semester 6 and 8 who have taken and passed auditing courses. The sampling technique used was purposive sampling. The research method used is quantitative research method. The data were obtained through questionnaires and measured using multiple regression analysis with processing through the SPSS 23 software. The results of this study indicate that compliance with attitudes and personality types have a significant positive effect on intention, subjective norms have a significant negative effect on intention while behavioral control has no effect on intention.